MnZn-BASED FERRITE AND MANUFACTURING METHOD OF THE SAME
A specific MNZN ferrite composition with controlled components and particle size stabilizes magnetic characteristics and reduces high-frequency losses, addressing performance issues under high magnetic fields.
Patent Information
- Application Number
- JP2024191181
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-10-02
AI Technical Summary
Existing MNZN ferrite materials experience high-frequency losses and changes in magnetic characteristics under high magnetic fields, which affect their performance in communication equipment and power supply applications.
The MNZN ferrite composition includes specific ratios of Fe2O3, ZnO, and MnO as main components, with additional additives like SiO2, CaO, Co2O3, and TiO2, and a controlled average crystal particle size of 4 μm or less, along with a sintering density of 4.8 g/cm³, to reduce high-frequency losses and stabilize magnetic characteristics under high magnetic fields.
The modified MNZN ferrite achieves reduced high-frequency losses and stable magnetic properties even under high magnetic fields, with core loss and volume loss minimized by suppressing magnetic wall movement and whirlpool currents.
Smart Images

Figure 2025016636000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an MnZn-based ferrite and a method for producing the same. [Background technology]
[0002] MnZn-based ferrite has properties such as high magnetic permeability, high magnetic flux density, and ease of magnetization even in a small magnetic field, and is widely used for communication equipment applications, power supplies, etc. Various studies have been conducted on MnZn-based ferrite to obtain properties according to applications (e.g., Patent Documents 1-2).
[0003] Patent Document 1 describes an MnZn-based ferrite sintered body that has low core loss over a wide temperature range at high frequencies of 300 to 500 kHz and small change in core loss over time in high-temperature environments, and contains specific amounts of main components consisting of Fe2O3, ZnO, and MnO, and specific amounts of subcomponents consisting of SiO2, CaCO3, Co3O4, ZrO2, and Ta2O5, has an average crystal grain size of 3 μm or more and less than 8 μm, and has a sintered body density of 4.65 g / cm 3 The above MnZn-based ferrite sintered bodies are disclosed.
[0004] Patent Document 2 discloses a low-loss Mn-Zn ferrite that contains Fe, Mn, and Zn as main components, Co, Ca, and Si as a first minor component, and a specific amount of a Va group element as a second minor component, and has an average crystal grain size of less than 3.2 μm and a volume resistivity of 1 Ω m or more, as an Mn-Zn ferrite that has low power loss over a wide temperature range and operating magnetic flux density even at high frequencies of 1 MHz or more. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 181242 [Patent Document 2] International Publication No. 2006 / 054749 Summary of the Invention [Problem to be solved by the invention]
[0006] There is a demand for further reduction in loss at high frequencies in MnZn ferrites. However, the present inventors have found that, depending on the method for reducing loss, the magnetic properties may change when a high magnetic field is applied.
[0007] The present invention is devised to solve the above-mentioned problems, and provides an MnZn-based ferrite capable of reducing loss at high frequencies and suppressing changes in magnetic properties in a strong magnetic field, and a method for producing the same. [Means for solving the problem]
[0008] The MnZn-based ferrite according to the present invention is It contains Fe2O3, ZnO and MnO as its main components. In 100 mol % of the main component, Fe2O3 is 53.2 to 56.0 mol %, ZnO is 3.0 to 12.0 mol %, and the remainder is MnO, The main component is 100% by mass, and the auxiliary components are 0.005 to 0.060% by mass of SiO2, 0.010 to 0.060% by mass of CaO, 0.10 to 0.40% by mass of Co2O3, and 0.05 to 0.30% by mass of TiO2. The average crystal grain size is 4 μm or less, Sintered density is 4.8g / cm 3 That's all.
[0009] One embodiment of the MnZn-based ferrite further contains 0.010 to 0.100 mass % of ZrO as an accessory component.
[0010] One embodiment of the MnZn-based ferrite has a core loss per unit volume (Pcv) of 1500 mW / cm at 25° C., 2 MHz, and 50 mT. 3 The following is the result.
[0011] One embodiment of the MnZn ferrite has a rate of change of unit core loss (Pcv) at 25° C., 2 MHz, and 50 mT, represented by the following formula (1), of 100% or less. Formula (1): (Pcv-Pcv0) / Pcv0×100 Here, Pcv0 is the unit core loss before the magnetic field is applied.
[0012] The method for producing MnZn-based ferrite according to the present invention is as follows: The method for producing MnZn-based ferrite according to the present invention comprises the steps of: After sintering, a process of mixing raw materials containing each main component so that, in 100 mol% of the main component, Fe2O3 is 53.2 to 56.0 mol%, ZnO is 3.0 to 12.0 mol%, and the remainder is MnO; adding raw materials containing each of the subcomponents so that the SiO2 content is 0.005 to 0.060 mass%, the CaO content is 0.010 to 0.060 mass%, the Co2O3 content is 0.10 to 0.40 mass%, and the TiO2 content is 0.05 to 0.30 mass% relative to 100 mass% of the main component after sintering; The resulting mixed powder is then crushed until it becomes a crushed powder having a D90 particle size of 1.2 μm or less.
[0013] One embodiment of the above-mentioned manufacturing method further includes a step of molding the crushed powder and heat treating it at 1050 to 1150°C. Effect of the Invention
[0014] The present invention provides an MnZn-based ferrite that can reduce loss at high frequencies and suppress changes in magnetic properties in a strong magnetic field, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The MnZn ferrite and the method for producing the same according to the present invention will be described below. In addition, unless otherwise specified, the slash "~" indicating a numerical range includes the lower limit and the upper limit.
[0016] [MnZn ferrite] The MnZn-based ferrite according to the present invention (hereinafter also referred to as the present MnZn-based ferrite) contains Fe2O3, ZnO, and MnO as main components, In 100 mol % of the main component, Fe2O3 is 53.2 to 56.0 mol %, ZnO is 3.0 to 12.0 mol %, and the remainder is MnO, The main component is 100% by mass, and the auxiliary components are 0.005 to 0.060% by mass of SiO2, 0.010 to 0.060% by mass of CaO, 0.10 to 0.40% by mass of Co2O3, and 0.05 to 0.30% by mass of TiO2. The average crystal grain size is 4 μm or less, Sintered density is 4.8g / cm 3 The present invention is characterized in that:
[0017] The present inventors have discovered a ceramic material containing the above-mentioned metal oxides in the above-mentioned specific ratios, with an average crystal grain size of 4 μm or less and a sintered density of 4.8 g / cm 3 The present invention was completed based on the findings that by adjusting the MnZn ferrite as described above, it is possible to reduce losses at high frequencies (particularly 1 MHz to 3 MHz) and also to suppress changes in magnetic properties after the application of a high magnetic field. The present inventors have found that MnZn-based ferrite with a hysteresis loop having perminvar characteristics can reduce losses at high frequencies. The MnZn-based ferrite with perminvar characteristics suppresses (pins) domain wall movement, thereby reducing residual losses associated with domain wall movement. However, when a high magnetic field is applied, there are cases where pinning of the domain walls is insufficient, and the mobility of the domain walls increases, resulting in insufficient loss reduction. On the other hand, the present MnZn-based ferrite contains each component in the above-mentioned specific ratio, and has a small crystal grain size of 4 μm or less, thereby reducing the number of domain walls in the crystal grains and reducing residual losses associated with domain wall movement. Specifically, the present MnZn-based ferrite has a core loss per unit volume (Pcv) of 1500 mW / cm at 25° C., 2 MHz, and 50 mT, for example. 3In addition, with the present MnZn-based ferrite, for example, the rate of change of the core loss per unit volume (Pcv) at 25° C., 2 MHz, and 50 mT, as expressed by the following formula (1), relative to before application of a magnetic field, can be suppressed to 100% or less. Formula (1): (Pcv-Pcv0) / Pcv0×100 Thus, the MnZn ferrite has the characteristic that it is possible to reduce loss at high frequencies even when a high magnetic field is applied, in the same way as when no high magnetic field is applied.
[0018] The present MnZn-based ferrite is composed mainly of Fe2O3, ZnO, and MnO. In the present MnZn-based ferrite, the main components are 100 mol % and include 53.2 to 56.0 mol % Fe2O3, 3.0 to 12.0 mol % ZnO, and the remainder (33.0 to 43.8 mol %) MnO.
[0019] By making Fe2O3 53.2mol% or more, preferably 53.5mol% or more, MnZn ferrite with high magnetic flux density can be obtained. On the other hand, by making Fe2O3 56.0mol% or less, preferably 55.0mol% or less, more preferably 54.8mol% or less, perminburization of MnZn ferrite is suppressed in combination with other components, and loss during application of a high magnetic field can be reduced.
[0020] By making the ZnO content 3 mol% or more, preferably 6 mol% or more, the perminburization of MnZn ferrite is suppressed in combination with other components, and the sinterability is excellent, and the crystal density is 4.8 g / cm 3 On the other hand, by making the ZnO content 12.0 mol % or less, preferably 11.0 mol % or less, a MnZn ferrite with high magnetic flux density can be obtained.
[0021] The MnZn ferrite also contains at least SiO2, CaO, Co2O3, and TiO2 as accessory components.
[0022] By making the SiO2 content 0.005% by mass or more, preferably 0.010% by mass or more, a grain boundary phase having high resistivity is sufficiently formed, and the generation of eddy current at high frequencies is suppressed. In addition, by containing SiO2, the mechanical strength of the MnZn ferrite is improved. On the other hand, by making the SiO2 content 0.060% by mass or less, preferably 0.050% by mass or less, the generation of SiO2 that becomes thick can be suppressed, and the deterioration of loss can be suppressed.
[0023] By making the CaO content 0.010% by mass or more, preferably 0.030% by mass or more, a grain boundary phase having high resistivity is sufficiently formed, suppressing the generation of eddy currents at high frequencies, while by making the CaO content 0.050% by mass or less, preferably 0.045% by mass or less, the amount of CaO remaining as an impurity is suppressed, and the deterioration of loss can be suppressed.
[0024] By setting the Co2O3 content to 0.10 mass% or more, preferably 0.20 mass% or more, it is possible to suppress loss in a high-temperature environment. On the other hand, by setting the Co2O3 content to 0.40 mass% or less, preferably 0.30 mass% or less, perminvarization is suppressed, and loss during application of a high magnetic field can be reduced.
[0025] By setting the TiO2 content to 0.05 mass% or more, preferably 0.10 mass% or more, perminvar formation is suppressed, and loss during application of a high magnetic field can be reduced. On the other hand, by setting the TiO2 content to 0.30 mass% or less, preferably 0.25 mass% or less, perminvar formation is suppressed, and loss during application of a high magnetic field can be reduced.
[0026] The MnZn-based ferrite may further contain other components within the range in which the effects of the present invention are achieved. Examples of other components include other metal oxides added as necessary and elements that are inevitably contained. Examples of other metal oxides include ZrO2, Ta2O5, Nb2O5, Bi2O3, and MoO3, and among these, ZrO2 is preferred. In addition, examples of elements that are inevitably included include C (carbon atom), P (phosphorus atom), and B (boron atom).
[0027] By making the ZrO2 content 0.01% by mass or more, preferably 0.04% by mass or more, a grain boundary phase having high resistivity is sufficiently formed, suppressing the generation of eddy currents at high frequencies.On the other hand, by making the ZrO2 content 0.1% by mass or less, preferably 0.08% by mass or less, the amount of ZrO2 remaining as an impurity is suppressed, and the deterioration of loss can be suppressed.
[0028] The total content of metal oxides and elements other than ZrO2 is preferably 0.1 mass% or less, and more preferably 0.01 mass% or less, relative to 100 mass% of the main component.
[0029] The present MnZn-based ferrite can be suitably used, for example, as a core material for an inductor used in a switching power supply circuit with a high switching frequency (for example, 1 to 3 MHz).In addition, since the present MnZn-based ferrite is suppressed from changing in magnetic properties even when a high magnetic field is applied, it can be suitably used, for example, in transformers and choke coils through which a large current may flow.
[0030] [Manufacturing method of MnZn ferrite] Next, one embodiment of a method for producing MnZn ferrite (hereinafter also referred to as the present production method) will be described. The present manufacturing method is a manufacturing method capable of suitably manufacturing the present MnZn-based ferrite, and may include at least a step (mixing step) of mixing raw materials containing each main component so that after sintering, in 100 mol% of the main component, the content is 53.2 to 56.0 mol% of Fe2O3, 3.0 to 12.0 mol% of ZnO, and the remainder is MnO; a step (adding step) of adding raw materials containing each subcomponent so that after sintering, the content is 0.005 to 0.060 mass% of SiO2, 0.010 to 0.060 mass% of CaO, 0.10 to 0.40 mass% of Co2O3, and 0.05 to 0.30 mass% of TiO2, relative to 100 mass% of the main component; and a step (crushing step) of crushing the obtained mixed powder until it becomes a crushed powder having a D90 particle size of 1.2 μm or less. This manufacturing method may further include, after the mixing step, a drying / granulation step of adding a binder to the mixed powder of the main components to form granules; a calcination step of calcining the obtained granules; a drying / granulation step of the crushed powder; a molding step of molding the crushed powder or its granules; and a heat treatment step (sintering step) of heat treating the molded body.
[0031] In the mixing step, the main components are mixed so that the main components after sintering have the composition of the present MnZn ferrite. The form of the main components before mixing is not particularly limited, but it is preferable that they are in a powder form from the viewpoint of easy handling and uniform mixing. The raw material powders of the main components are mixed and crushed as necessary to obtain a mixed powder. The mixing and crushing method may be appropriately selected from known methods. Specific examples include an attritor and a bead mill. The particle size of the mixed powder is not particularly limited, but it is preferable to adjust the median diameter D50 to 0.5 μm to 1.5 μm from the viewpoint of uniformity. The particle size D50 and D90 described later are the particle size (D50) and particle size (D90) at which the cumulative frequency of the particle size is 50% and 90%, respectively, when the particle size distribution of the target particles is measured. The particle size distribution of the mixed powder can be measured with a particle size distribution measuring device.
[0032] The mixed powder of the main components may be subjected to a drying / granulation process. In the drying / granulation process, for example, 0.5 to 1 part by mass of a binder such as polyvinyl alcohol is added to the mixed powder obtained in the mixing process when the total mass of the mixed powder is 100 parts by mass, and the mixture is sprayed using a spray dryer or the like to obtain granules. The obtained granules may then be calcined, for example, at 750° C. for about 1 hour in an air atmosphere to produce a calcined product (calcination step).
[0033] Next, the auxiliary components are added to the calcined product so that the auxiliary components after sintering have the composition of the present MnZn ferrite. The form of the auxiliary components before addition is not particularly limited, but it is preferable that the auxiliary components are in a particulate form from the viewpoint of easy handling and uniform mixing.
[0034] After adding the subcomponents, the resulting mixed powder is crushed to obtain crushed powder. Crushing may be appropriately adjusted so that the average crystal grain size of the resulting MnZn-based ferrite is 4 μm or less. For example, the calcined product is crushed until the D90 of the grain size after crushing is 1.2 μm or less.
[0035] In the drying and granulation process, 0.5 to 1.0 parts by mass of a binder such as polyvinyl alcohol is added to the crushed powder obtained in the crushing process when the total mass of the crushed powder is 100 parts by mass, and granules are obtained by spraying with a spray dryer, etc. At this time, it is desirable that the median diameter D50 of the granules is 40 μm or more and 200 μm or less.
[0036] In the molding process, the granules obtained in the drying and granulation process are molded into a predetermined shape. The predetermined shape may be designed according to the application, etc. For example, the granules are molded into a toroidal core with an outer diameter of 19 mm, an inner diameter of 13 mm, and a height of 11 mm.
[0037] The molded granules are heat-treated to form a sintered body (MnZn ferrite). The heat treatment (sintering) conditions are preferably 1050 to 1150°C for several hours. By heat-treating at 1050°C or higher, the sintered density is 4.8g / cm 3On the other hand, by performing heat treatment at 1150°C or less, it becomes easier to achieve an average crystal grain size of 4 μm or less.
[0038] According to the above manufacturing method, the average crystal grain size is 4 μm or less, and the sintered density is 4.8 g / cm 3 As described above, MnZn-based ferrite is suitably produced. EXAMPLES
[0039] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these descriptions.
[0040] [Example 1] Each raw material powder was weighed and mixed so that the Fe2O3 content after sintering was 54.0 mol%, the ZnO content was 10.0 mol%, and the MnO content was 36.0 mol%, totaling 100 mol%. 0.5 parts by mass of polyvinyl alcohol was added to the total mass of the above mixture of 100 parts by mass, and sprayed with a spray dryer to obtain granules. Next, the granules were calcined in an air atmosphere at 750°C for 1 hour to obtain a calcined product. Next, each raw material powder was added as a subcomponent so that the main component was 100% by mass, and the following subcomponents were added: 0.03% by mass of SiO2, 0.04% by mass of CaO, 0.2% by mass of Co2O3, 0.2% by mass of TiO2, and 0.08% by mass of ZrO2. Next, in the crushing process, the mixture of the calcined product and additives was crushed in a crusher so that the particle size after crushing had a D90 of 1.2 μm or less to obtain crushed powder. Next, in the drying and granulation process, 1 part by mass of polyvinyl alcohol was added to this crushed powder per 100 parts by mass of the total mass of the crushed powder, and granules were obtained by spraying with a spray dryer. Next, in the molding and sintering processes, the granules were molded into a toroidal core with an outer diameter of 16 mm, an inner diameter of 10 mm, and a height of 5 mm, and sintered at 1100°C to obtain a sintered body (MnZn-based ferrite).
[0041] [Examples 2 to 16] The MnZn-based ferrites of Examples 2 to 16 were obtained in the same manner as in Example 1, except that the raw materials were mixed and added so that the content ratios of the main components and subcomponents after sintering were as shown in Table 1.
[0042] [Comparative Example 1] An MnZn-based ferrite of Comparative Example 1 was obtained in the same manner as in Example 1, except that the crushing time in Example 1 was shortened and the particle size D90 of the powder after crushing was set to 4.82 μm.
[0043] [Comparative Examples 2 to 12] The MnZn-based ferrites of Comparative Examples 2 to 12 were obtained in the same manner as in Example 1, except that the raw materials were mixed and added so that the content ratios of the main components and subcomponents after sintering were as shown in Table 1.
[0044] <Evaluation> The crushed particle size D90 was determined by measuring the slurry of crushed powder obtained in the manufacturing process of the above-mentioned Examples and Comparative Examples using a wet particle size distribution measuring device. The average grain size was calculated by image analysis of the images obtained by mirror-polishing each of the MnZn-based ferrites obtained in the examples and comparative examples, dissolving the grain boundary phase by etching, and observing the images with a microscope. The measurement was performed on 100 grains for each. The sintered density was measured by the Archimedes method. In addition, the Pcv and Pcv0 of the MnZn ferrite were measured by a BH analyzer, and the Pcv change rate was calculated by the above formula (1). The results are shown in Table 1.
[0045] [Table 1]
[0046] [Summary of results] The main component (100 mol%) is 53.2-56.0 mol% Fe2O3, 3.0-12.0 mol% ZnO, and the remainder is MnO. The main component (100 mass%) contains, as secondary components, 0.005-0.060 mass% SiO2, 0.010-0.060 mass% CaO, 0.10-0.40 mass% Co2O3, and 0.05-0.30 mass% TiO2. The average crystal grain size is 4 μm or less, and the sintered density is 4.8 g / cm. 3 The MnZn ferrites of Examples 1 to 16 have a core loss per unit volume (Pcv) of 1500 mW / cm at 25° C., 2 MHz, and 50 mT. 3 It was also shown that the rate of change in Pcv from before the application of the magnetic field was 100% or less. From the above, it became clear that this MnZn ferrite can reduce both the loss at high frequencies and the change in magnetic properties under a strong magnetic field.
Claims
1. Fe 2 O 3 and ZnO and MnO as main components, In 100 mol% of the main components, Fe 2 O 3 is 53.2 to 56.0 mol %, ZnO is 3.0 to 12.0 mol %, and the remainder is MnO; As a subcomponent, SiO 2 0.005 to 0.060 mass%, CaO 0.010 to 0.060 mass%, Co 2 O 3 0.10 to 0.40 mass% of TiO 2 Contains 0.05 to 0.30 mass% The average crystal grain size is 4 μm or less, Sintered density is 4.8g / cm 3 That is all for the MnZn-based ferrite.
2. The MnZn-based ferrite according to claim 1, further comprising 0.010 to 0.100 mass % of ZrO as an accessory component.
3. Core loss per unit volume (Pcv) at 25°C, 2MHz, and 50mT is 1500mW / cm 3 The MnZn-based ferrite according to claim 1 or 2, wherein:
4. 4. The MnZn-based ferrite according to claim 1, wherein a rate of change in unit core loss (Pcv) at 25° C., 2 MHz and 50 mT, as represented by the following formula (1), relative to before application of a magnetic field is 100% or less. Formula (1): (Pcv-Pcv 0 ) / Pcv 0 ×100 However, Pcv 0 is the unit core loss before application of the magnetic field.
5. A method for producing MnZn-based ferrite according to any one of claims 1 to 4, After sintering, Fe in 100 mol% of the main component 2 O 3 mixing raw materials containing each main component so that the content of each main component is 53.2 to 56.0 mol %, ZnO is 3.0 to 12.0 mol %, and the remainder is MnO; After sintering, SiO 2 0.005 to 0.060 mass%, CaO 0.010 to 0.060 mass%, Co 2 O 3 0.10 to 0.40 mass% TiO 2 adding a raw material containing each of the subcomponents so that the content is 0.05 to 0.30 mass %; The method for producing MnZn-based ferrite further comprises a step of crushing the obtained mixed powder until the mixed powder has a D90 particle size of 1.2 μm or less.
6. The method for producing MnZn ferrite according to claim 5, further comprising the steps of molding the crushed powder and heat treating the molded powder at 1050 to 1150°C.
Citation Information
Patent Citations
Low-loss Mn-Zn ferrite and, electronic part and switching power supply utilizing the same
CN101061080A
Ferrite core, electronic component and power supply
CN106486237A
Method for producing Mn-Zn ferrite
CN1649039A
Sintered ferrite with crystallite particle and manufacture thereof
JP1994333724A
METHOD OF MANUFACTURING MnZn FERRITE AND MnZn FERRITE
JP2005213100A